Peningkatan Kreativitas dan Hasil Belajar IPA MelaluiPenerapan Strategi Pembelajaran SAVI pada Siswa Kelas IV SD Negeri Sanggang 02, Bulu, Sukoharjo Tahun 2015/2016 - Sunarsih, Ayu Retnoningsih Rahayu (2016)
In teaching and learning in the school teachers have an important role in determining the success of students. This study aims to: (1) Enhancing creativity learn science through SAVI strategies, (2) Improve learning outcomes IPA channeled through SAVI strategy. This type of research is a classroom action research (PTK). The subjects of this study were teachers and students of class IV Elementary School Sanggang 02 totaling 19 students. The technique of collecting data through interviews, observation, methods of testing, and documentation. The data analysis technique used in this study is an interactive model that includes: data reduction, data presentation, and conclusion, withdrawal or verification. The results showed an increase in creativity and science learning outcomes through the application of learning strategies SAVI at Elementary School fourth grade students Sanggang 02 years 2015/2016. Increased creativity learning as follows: (a) high self-confidence has risen 8 students or 42.10% in pre-cycle, 14 students or 73.68% in the first cycle, and 17 students or 89.47% in the second cycle , (b) issue an opinion Dare has risen 5 students or 26.31% in pre-cycle, 14 students or 73.68% in the first cycle, and 17 students or 89.47% in the second cycle, (c) Implementing the right job time has risen 6 students or 31.57% in pre-cycle, 13 students or 68.42% in the first cycle, and 16 students or 84.21% in the second cycle, (d) Lively, tenacious, and not despair experienced ie an increase of 6 students or 31.57% in pre-cycle, 12 students or 63.15% in the first cycle, and 16 students or 84.21% in the second cycle, (e) Do not rely on others (independently) has risen 7 students or 36.84% in pre-cycle, 12 students or 63.15% in the first cycle, 16 students or 84.21% in the second cycle, (f) Glad in learning activities 6 students or 31.57% on a pre-cycle , 11 students or 57.89% in the first cycle, and 15 students or 78.94% in the second cycle. Improved learning outcomes in IPA as follows: prior to the action (pre-cycle) an average of 52.63% of student learning outcomes, then the first cycle reaches 73.68%, and the second cycle increased to 89.47%, meaning most students has been able to improve the value of the above KKM ≥70. From this study it can be concluded through the application of learning strategies SAVI can increase creativity and science learning outcomes in grade IV Sanggang SD Negeri 02, Fur, Sukoharjo year 2015/2016. Keywords: Creativity, learning outcomes, IPA, learning strategies SAVI